OC-023 Salvage endoscopic resection of scarred polyps after failed previous endoscopic resection attempt: sense study. (22nd June 2015) - Chedgy, FJQ; Bhattacharyya, R; Kandiah, K; Longcroft-Wheaton, G; Bhandari, P
Abstract : Introduction: Current standard of care for recurrent/residual polyps after previous endoscopic resection is surgery. This study analyses the outcomes of salvage endoscopic resection of polyps with severe scarring following a previously failed endoscopic resection. Method: Prospective cohort study of patients referred to a Tertiary-centre for resection of scarred polyps with failed previous endoscopic resection attempts. Resection techniques: ESD knife and Snare combination (Knife Assisted Resection, KAR) or Snare and APC assisted resection (SAR). Results: We identified 64 consecutive patients referred to us following a previously failed endoscopic resection attempt. All these patients had severely scarred polyps which were being considered for surgery at the referring centre. The mean polyp size 46 mm (20–150 mm). 83% were left-sided and 17% right–sided. 67% of resections were performed by KAR with mean polyp size 50 mm. 33% of resections were by SAR with mean polyp size 38 mm. Referral to surgery : 2/64 for technically difficult so no attempt made, 5/64 for cancer. Endoscopic follow up and cure : mean follow up of 3 years (range:1–8 years), 97% overall cure rate which was the same for left and right sided lesions as well as KAR and SAR. The only complication was bleeding seen in 3 patients (4.6%). Cost saving: Had all 64 patients been sent for surgery the total cost would have been £343, 224. The total cost of the endoscopic approach, including the cost of patients requiring surgery, was £149, 820 representing an average cost saving of £3021.94 per patient. Conclusion: Severely scarred polyps due to failed previous endoscopic mucosal resection attempts can be successfully treated by experts. The techniques of KAR and SAR are equally effective when used for appropriate polyps. The complication rate is low. Further recurrence after first salvage resection can be treated successfully. Surgery can be avoided in most patients and an endoscopic approach is very cost effective. We would therefore, advocate an aggressive endoscopic resection strategy over surgery when dealing with severely scarred polyps. Disclosure of interest: None Declared.